Multi-nested antiresonant hollow-core fiber with ultralow loss and single-mode guidance - Wang, Yuxi (2023)
We propose an antiresonant hollow-core fiber design that exhibits ultralow loss and exceptional single modedness at 1.55 µm. In this design, the confinement loss of less than 10-6 dB m-1 can be obtained with excellent bending performance even at a tight bending radius of 3 cm. At the same time, a record-high higher-order mode extinction ratio of 8 × 105 can be achieved in the geometry by inducing strong coupling between the higher-order core modes and cladding hole modes. These guiding properties make it an excellent candidate for applications in hollow-core fiber-enabled low-latency telecommunication systems.